Learnings from a German research network on substance use among refugees (PREPARE) with a focus on an intervention to improve emotion regulation - Milin, Sascha; Behrendt, Malte; Bari, Melav; López Atanes, Mayte; Tekeli, Muhammed Refik; Zurhold, Heike; Hiller, Philipp; Lotzin, Annett; Schäfer, Ingo (Addicta: The Turkish Journal on Addictions, 2026)
Refugees face a unique constellation of pre-, peri-, and post-migration stressors that can increase vulnerability to hazardous substance use while simultaneously limiting access to appropriate care. To address this gap, the PREPARE consortium was established as the first coordinated German research network on substance use among refugees, combining empirical assessment, diagnostic innovation, and intervention development. This article provides an overview of the network and synthesizes cross-project learnings with a particular focus on Subproject 4 (STARC-SUD), an emotion-regulation–based group intervention adapted for refugees with hazardous alcohol or drug use.Across multiple sites, PREPARE identified substantial barriers to recruitment and engagement, including stigma, legal insecurity, language difficulties, and the structural conditions of communal accommodation. The adaptation and translation of screening instruments improved diagnostic accuracy, while iterative modifications of STARC-SUD enhanced cultural fit and feasibility. Early implementation experiences highlight the importance of trust-building, flexible delivery formats, and close cooperation with community actors. The Sucht-und-Flucht.de platform (https://www.sucht-und-flucht.de/en/) emerged as a central dissemination tool, providing multilingual materials, diagnostic instruments, and project information to practitioners and supporting long-term knowledge transfer.The preliminary observations from the ongoing trial underscore the need for integrated, culturally sensitive, and trauma-informed approaches within European addiction-care systems. PREPARE demonstrates the potential of emotion-regulation interventions for refugee populations and points to the importance of sustained, multi-level strategies involving research, practice, and policy to improve access and outcomes for displaced individuals affected by substance use.
Keywords: addictions to alcohol; addictions to drugs; alcohol; germany; mental heath; prevention; refugees